Contents of Logopedic Rhythm Exercises Conducted with Children Who Stutter (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article presents the complex approach to stuttering elimination, the main tasks in the complex approach, the use of speech therapy techniques, the complex method of rehabilitation of stutterers, and logarithmic exercises with stuttering children.